Measuring Urban Form Units: Alternative for Characterizing Urban Growth Pattern in Yogyakarta Urbanized Areas - Mutiasari Kurnia Devi; Lulu Mari Fitria; Muhammad Sani Roychansyah; Yori Herwangi (Faculty of Geography, Universitas Gadjah Mada, 2020)
Yogyakarta is one of city in Indonesia which experience urban agglomeration called by Yogyakarta Urbanized Area (YUA). In this paper, identified the characters of each part of YUA by examining its urban form unit. This paper assesses the characteristics of urban forms distributed within YUA. Quantitative measurements were proposed for classifying the urban form typologies. Density, diversity, and accessibility were used to represent the urban form characteristic., the typologies are classified into three groups which are low compact, middle compact, and high compact. The result shows that the majority areas in YUA are grouped into middle compact typology where most of them are located in the city of Yogyakarta administrative area. Meanwhile, the areas, categorized as low compact typology, are in the hinterland area of Yogyakarta. High compact typology are concentrated in the centre of YUA where it has the highest activity concentration for the whole urban structure context. This study discovers that characterizing the urban growth patterns using quantitative method can distinguish urban form. At the end, this paper provides an important note about the distribution of urban form typology in the agglomeration area and, in the future, can be used to design urban policies, especially in the utilization of urban space.